Age-Related Autoregulatory Dysfunction and Cerebromicrovascular Injury in Mice with Angiotensin II-induced Hypertension. Issue 11 (November 2013) - Toth, Peter; Tucsek, Zsuzsanna; Sosnowska, Danuta; Gautam, Tripti; Mitschelen, Matthew; Tarantini, Stefano; Deak, Ferenc; Koller, Akos; Sonntag, William E; Csiszar, Anna; Ungvari, Zoltan
Hypertension in the elderly substantially contributes to cerebromicrovascular damage and promotes the development of vascular cognitive impairment. Despite the importance of the myogenic mechanism in cerebromicrovascular protection, it is not well understood how aging affects the functional adaptation of cerebral arteries to high blood pressure. Hypertension was induced in young (3 months) and aged (24 months) C57/BL6 mice by chronic infusion of angiotensin II (AngII). In young hypertensive mice, the range of cerebral blood flow autoregulation was extended to higher pressure values, and the pressure-induced tone of middle cerebral artery (MCA) was increased. In aged hypertensive mice, autoregulation was markedly disrupted, and MCAs did not show adaptive increases in myogenic tone. In young mice, the mechanism of adaptation to hypertension involved upregulation of the 20-HETE (20-hydroxy-5, 8, 11, 14-eicosatetraenoic acid)/transient receptor potential cation channel, subfamily C (TRPC6) pathway and this mechanism was impaired in aged hypertensive mice. Downstream consequences of cerebrovascular autoregulatory dysfunction in aged AngII-induced hypertensive mice included exacerbated disruption of the blood–brain barrier and neuroinflammation (microglia activation and upregulation of proinflammatory cytokines and chemokines), which were associated with impaired hippocampal dependent cognitive function. Collectively, aging impairs autoregulatory protection in the brain of mice with AngII-induced hypertension, potentially exacerbating cerebromicrovascular injury and neuroinflammation.